ZnO/PBAT nanocomposite films: Investigation on the mechanical and biological activity for food packaging. (15th July 2016) - Venkatesan, Raja; Rajeswari, Natesan
Abstract : Packaging of foods in high barrier materials is essential to attain food safety. Nanocomposite technology is leading in search of the earlier said kind of packaging materials. The role of zinc oxide (ZnO) loadings on poly(butylene adipate‐co‐terephthalate) (PBAT) structure were investigated, in addition to that packaging properties such as barrier, thermal, and mechanical properties were studied. Antimicrobial films are developed based on PBAT and ZnO nanoparticles. The nanocomposites exhibits a significant increase in the mechanical and thermal stability. The resulting PBAT/ZnO nanofilms show superior antimicrobial activity against Escherichia coli and Staphylococcus aureus . Copyright © 2016 John Wiley & Sons, Ltd.